Biofísica médica: exercícios práticos - J. J. Pedroso de Lima (Ensino, 2019)
The Book of Medical Biophysics. Practical exercises intends to be an auxiliary for the study of this matter. It constitutes the compilation of the exercises developed by the set of assistants since the Faculty of Medicine of the University of Coimbra has decided to invest in specific training in biophysics. The issues for which problems have been made relate to 3 chapters: mass transport through membranes, fluids and radioactivity. All problems developed are aimed at biomedical applications, and assist in the practical comprehension of the same themes presented in the book Biophysics Medical, authored by João José Pedroso de Lima, also published by the Coimbra University Press and representing the recommended book for the discipline. In fact, the theoretical explanations are even referred to this book. In all chapters there are problems resolved and commented, other problems for which solutions are present and yet another type that are proposed problems, but no solution presented. We hope that this book will be a good helper for the study of biophysics.